“Witch doctors” or professionals? The graduates of Mexico´’s first intercultural university and the struggle for legitimacy - Lloyd, Marion (Education Policy Analysis Archives, 2021)
Since 2003, the Mexican government has opened 11 intercultural universities serving a total of 15,000 students, a majority of whom are members of Mexico´s Indigenous minority. While there is a growing body of work analyzing the intercultural model from public policy and theoretical perspectives, few studies focus on the experiences of the students and graduates of these institutions. In this article, I share the findings of one such study of the Intercultural University of Mexico State, the pioneer of the intercultural universities. Through interviews with graduates, students, and deans of three undergraduate intercultural programs, I seek to answer a central question, which is rooted in critical and decolonial theory: To what degree does the intercultural model achieve its stated mission of empowering Indigenous students and to what degree does it contribute to the reproduction of inequality? In general, the findings are mixed. While many students share experiences of discrimination in the workplace, and even being derided as “witch-doctors,” they argue that attending an institution with a critical mass of Indigenous students has empowered them personally and professionally, transformed their cultural identities, and given them a new appreciation for their Indigenous roots.